Visible-Light Photocatalytic Ugi/Aza-Wittig Cascade towards 2-Aminomethyl-1,3,4-oxadiazole Derivatives - Russo, Camilla; Cannalire, Rolando; Luciano, Paolo; Brunelli, Francesca; Tron, Gian Cesare; Giustiniano, Mariateresa (Synthesis, 2021)
A new visible-light photocatalytic multicomponent reaction (MCR) involving N-alkyl-N-methylanilines, N-isocyanoiminotriphenylphosphorane, and carboxylic acids leading to 1,3,4-oxadiazole derivatives is reported. The developed mild reaction conditions enable a broad substrate scope and good functional group tolerance, as further highlighted in the late-stage functionalization of amino acids and drugs. Additionally, a two-step one-pot protocol for the synthesis of non-symmetrical diacylhydrazines is also reported.
Keywords: photoredox catalysis; isocyanide chemistry; Ugi reaction; aza-Wittig reaction; multicomponent reactions; 1,3,4-oxadiazoles